Kegiatan pengolahan air sungai dengan metode kougulasi dan flokuasi dalam upaya pencegahan stunting di Desa Sumber Jaya Kecamatan Timang Gajah Kabupaten Bener Meriah - Aditama, Wiwit; Zukfikar, Zulfikar; Khairunnisa, Khairunnisa; PS, Budi Arianto; Nindia, Yuni; Sari, Arnida; Samosir, Ainun (Jurnal PADE: Pengabdian & Edukasi, 2024)
The location of the village in a highland area makes it difficult to get groundwater, to fulfil daily needs, namely drinking, bathing, washing. Meanwhile, to fulfil these water needs, residents utilise rainwater and river water. Rainwater sources can only be used to meet the needs during the rainy season, while river water is used by residents by piping from the mountain where there is a small river that does not always get clear water because it is carried away by soil material, especially during the rainy season the water becomes cloudy and the water reservoir must always be cleaned because there is silt or soil carried by water. This service will be carried out, namely counselling activities and river water treatment practices with simple cougulation and flocculation methods to always get clear water. The target of the service is villagers. Activities were carried out in May 2024, with site preparation activities and permits and procurement of materials, implementation of lecturer and student activities and assisted by the community in the form of counseling and at the same time practice in making filters and natural cogulation, participants who attended were generally attended by family heads and housewives. And the ability of the community to treat water simply and the ability to make natural coagulation was obtained.